Glucagon- and insulin-immunopositive endocrine cells in porcine extrahepatic bile ducts and gallbladder - Stefanov, Ivaylo Stefanov; Stefanov, Stefan Ivaylov; Gulubova, Maya Vladova (Frontiers in Veterinary Science, 2023)
Pancreatic β-cells and α-cells have been found in the murine extrahepatic biliary ducts but not in the gallbladder. However, there has been no information in the specialized literature about the presence of glucagon and insulin expressing endocrine cells in porcine bile ducts and gallbladder. Aim: We aimed to perform immunohistochemical study to identify glucagon and insulin positive cells and their distribution in the porcine extrahepatic biliary ducts and gallbladder. Method: The immunohistochemical method was used to detect the presence and distribution of glucagon and insulin positive endocrine cells in ductus hepaticus communis, ductus choledochus, ductus cysticus and vesica fellea of male pigs. Chromogranin A was used as a typical marker for endocrine cells. Results: The density of chromogranin A-, glucagon-and insulin positive cells per field was the largest in common bile duct, followed by common hepatic duct, cystic duct and gallbladder. The three types of endocrine cells showed specific localization in the superficial and deep glands of the studied organs. Conclusion and clinical importance: The distribution of glucagonand insulin immunopositive endocrine cells in the porcine extrahepatic biliary tract was established for the first time, as a new source of these hormones. The presence of α-and β-cells in the epithelium of extrahepatic bile ducts can be applied in treatment of diabetes taking into account the possibility to reprogram the biliary epithelium to mentioned pancreatic endocrine cell types. There are 1 Figure and 1 Table.